PENGEMBANGAN MEDIA AUDIO VISUAL BERBASIS KINEMASTER TERHADAP HASIL BELAJAR SISWA PADA MATA PELAJARAN IPAS KELAS V SD - Zulfiana Ramadhani Hasibuan; Safrida Napitupulu (STKIP Subang, 2025)
The development of Kinemaster-based audio visual media in science and science subjects in class V elementary school was motivated by the use of media or teaching materials that were not yet optimal and varied, there was no use of audio visual learning media based on Kinemaster in science subjects in class V elementary school, and student learning outcomes in There are still many science subjects which are below the criteria for achieving learning objectives (KKTP), which is 75. This research aims to develop Kinemaster-based audio visual media in science subjects for fifth grade elementary school to produce appropriate learning media and find out student learning outcomes after using audio media. Kinemaster based visuals. This research uses Research and Development using the ADDIE development model through 5 stages, namely analysis, design, development, implementation and evaluation. The subjects in this research were material experts, media experts, teachers and 28 class V students at UPT SPF SDN 106184 Sekip, Lubuk Pakam District. Data collection techniques in this research used observation, questionnaires, tests and documentation. Data analysis techniques are qualitative and quantitative descriptive analysis techniques. The results of the research show that the Kinemaster-based audio visual media product for grade V elementary school science subjects that has been developed and published via the YouTube application obtained a product validation data value, namely by material expert validators of 90.9% in the